2013
DOI: 10.1161/circulationaha.112.135046
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes After the Arterial Switch Operation for D-Transposition of the Great Arteries

Abstract: Background— Data regarding long-term outcomes after the arterial switch operation for D-transposition of the great arteries are scarce. Methods and Results— A single-institution retrospective cohort study was conducted to assess cardiovascular outcomes after an arterial switch operation between 1983 and 1999. Patients without follow-up visits within 3 years were contacted and secondary sources of information obtained. Overall, 400 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
238
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(262 citation statements)
references
References 42 publications
(43 reference statements)
15
238
3
6
Order By: Relevance
“…Importantly, none of these coronary abnormalities was detected on history and/or non-invasive studies including ECG and echocardiogram, and only 1 patient had positive screening on EST and MPI (patient 4). Although Khairy et al recently reported a relatively low incidence of late coronary complications after ASO in a larger single-center study, 30 the present results suggest that an occurrence of late coronary events including sudden cardiac death is not insignificant and consistent with the reports by other groups. 18,20,31 Whereas the clinical significance of trivial-mild coronary abnormalities is not entirely clear, some coronary vascular changes may be progressive.…”
Section: Methodssupporting
confidence: 91%
“…Importantly, none of these coronary abnormalities was detected on history and/or non-invasive studies including ECG and echocardiogram, and only 1 patient had positive screening on EST and MPI (patient 4). Although Khairy et al recently reported a relatively low incidence of late coronary complications after ASO in a larger single-center study, 30 the present results suggest that an occurrence of late coronary events including sudden cardiac death is not insignificant and consistent with the reports by other groups. 18,20,31 Whereas the clinical significance of trivial-mild coronary abnormalities is not entirely clear, some coronary vascular changes may be progressive.…”
Section: Methodssupporting
confidence: 91%
“…4 The initial short follow-up showed satisfactory results of ASO in comparison with the Mustard and Senning correction, but long-term results have only recently been reported. [5][6][7][8] The patient population with Mustard and Senning correction is now well into adulthood, making longterm follow-up possible. The population of patients with Mustard and Senning correction represents a clinical challenge and can provide us with important insight into the consequences of having a morphological right ventricle as a systemic ventricle.…”
mentioning
confidence: 99%
“…(31) Patients with repaired congenital heart disease and pulmonary vascular disease remain at increased risk of adverse outcome.…”
Section: Volume 13 Numbermentioning
confidence: 99%
“…Prior to the availability of targeted therapies, a single-center cohort study showed that the estimated median survival of children and adults with idiopathic pulmonary arterial hypertension were similar (4.12 versus 3.12 years, respectively). (31) Current 5-year survival of idiopathic pulmonary arterial hypertension and pulmonary arterial hypertension associated with congenital heart disease on targeted pulmonary vasodilators are reported to be 71 -75%.…”
Section: Volume 13 Numbermentioning
confidence: 99%